Implementation of Online Learning Applications in SD Bina Kreasi Mandiri Bekasi: Infrastructure Effect Analysis - Netti Natarida Marpaung (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Online learning activities are very useful in the era of the Covid-19 pandemic where face-to-face teaching and learning activities cannot be carried out. So online learning is very useful today, teachers or students are required to learn a lot using technology. The purpose of this study was to determine how much influence and linkage of infrastructure to the application of online learning (Online) in SD Swasta Bina Kreasi Mandiri Bekasi. Data was collected through samples by means of random sampling from the population, and sampling to represent the entire population was carried out through interviews, observations, and questionnaires. The method used in this research is descriptive analysis method. The results of the t test have a significant effect less than 0.05, namely (0.00 < 0.05), so it can be concluded that infrastructure affects the effectiveness of online learning at SD Bina Kreasi Mandiri, thus the hypothesis is accepted with strong significance.